Composite photovoltaic structure and method for manufacturing the same
By stacking the first and second photovoltaic units in parallel on the transparent substrate, the composite photovoltaic structure is designed, and the problem of low photoelectric conversion efficiency of thin-film solar cells in low illumination environments is solved, thereby increasing the current amount and reducing process costs are achieved.
Patent Information
- Application Number
- CN201910616645.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-07-09
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2039-07-09
AI Technical Summary
The existing thin-film solar cells have low photoelectric conversion efficiency in low illumination environments, resulting in insufficient current output.
A composite photovoltaic structure is designed to increase the photoelectric reaction area of the concentrating gain and increase the current by stacking the first and second photovoltaic units in parallel on a transparent substrate. The structure includes a transparent substrate, a transparent electrode layer, a transparent conductive layer and an insulating layer, and the materials of each layer are formed by slit coating and hot air drying technology.
Without increasing the overall structural thickness, the photoelectric reaction area and current volume are greatly improved, and the process cost is low, making it suitable for small-volume product applications.
Smart Images

Figure CN112216795B_ABST
Abstract
Description
Technical Field
[0001] The present invention is related to solar photovoltaic technology and aims to provide a composite photovoltaic structure that can significantly improve the all-round focusing gain photoelectric reaction area, effectively increase the current, does not affect the overall structure thickness, and has a low process cost, as well as a related composite photovoltaic structure manufacturing method. Background Art
[0002] Research on thin-film batteries is a highly anticipated direction in renewable energy. Although most commercial solar cells today use silicon as their main material, thin-film batteries have attracted attention from the industry and academia due to their simple manufacturing process, light material, and flexibility.
[0003] At present, when preparing thin-film batteries, coating can be used as a technical means to prepare solar cell thin films. Its advantage is that it can make the film have better flatness and uniformity. Furthermore, the R2R (Reel-to-Reel, or Roll-to-Roll) process is a technology with the potential to be used for large-area preparation of solar cells. It has been used in the industry, for example, in the preparation of a flexible display. Based on the "soft" characteristics of flexible displays, the R2R process can be well matched with its operation, so that these products with advantages such as plasticity, light weight, and impact resistance can be produced at a lower cost.
[0004] There are many types of thin-film solar cell photoelectric conversion devices in terms of structure, one of which is called organic polymer photovoltaic structure or perovskite photovoltaic structure. Figure 1 As shown, a photovoltaic unit 12 is mainly provided on a transparent substrate 11, an upper surface layer 123 and a lower surface layer 121 of the photovoltaic unit 12 are respectively a transparent electron transfer layer and a transparent hole transfer layer, and a transparent active layer 122 is provided between the upper surface layer 123 and the lower surface layer 121.
[0005] Among them, a first transparent electrode layer 131 and a second transparent electrode layer 132 are provided on the surface of the transparent substrate 11 to form insulation, the photovoltaic unit 12 is provided on the second transparent electrode layer 132, a transparent conductive layer 141 electrically connected to the first transparent electrode layer 131 is covered on the upper surface 123 of the photovoltaic unit 12, and an insulating layer 142 is provided between the side of the photovoltaic unit 12 and the transparent conductive layer 141.
[0006] similar Figure 1The conventional photovoltaic structure shown has many advantages such as a wide spectrum of light that can be adapted to photoelectric conversion, a thin structure, the ability to operate under process conditions below 180°C, and the aforementioned low-illuminance photoelectric conversion; however, in a low-illuminance environment, it is limited by the low illumination of the incident light source, and the converted current output is low even at an effective high photoelectric conversion efficiency. Summary of the invention
[0007] In view of this, the main purpose of the present invention is to provide a composite photovoltaic structure that can significantly improve the all-round focusing gain photoelectric reaction area, effectively increase the current, does not affect the overall structure thickness, and has a low process cost, as well as a related composite photovoltaic structure manufacturing method.
[0008] The composite photovoltaic structure of the present invention comprises a first photovoltaic unit on a transparent substrate, a second photovoltaic unit connected in parallel with the first photovoltaic unit is stacked on the first photovoltaic unit; the upper surface layer and the lower surface layer of the first photovoltaic unit and the second photovoltaic unit are respectively a transparent electron transfer layer and a transparent hole transfer layer, and the first photovoltaic unit and the second photovoltaic unit are each provided with a transparent active layer between their upper surface layer and lower surface layer; wherein: a first transparent electrode layer and a second transparent electrode layer are provided on the surface of the transparent substrate to form an insulated and separated relationship from each other, and the first photovoltaic unit is provided on the second transparent electrode layer in a state that its lower surface layer contacts the second transparent electrode layer; the upper surface layer of the first photovoltaic unit is covered with a transparent active layer electrically connected to the first transparent electrode layer; The second photovoltaic unit is provided on the first transparent conductive layer in a state where its lower surface is in contact with the first transparent conductive layer; the upper surface of the second photovoltaic unit is covered with a second transparent conductive layer electrically connected to the second transparent electrode layer; the first transparent conductive layer extends along the side of the first photovoltaic unit to the first transparent electrode layer, and a first insulating layer is provided between the side of the first photovoltaic unit and the first transparent conductive layer; the second transparent conductive layer extends along the side of the second photovoltaic unit, the side of the first transparent conductive layer and the side of the first photovoltaic unit to the second transparent electrode layer, and a second insulating layer is provided between the side of the second photovoltaic unit, the side of the first transparent conductive layer and the side of the first photovoltaic unit and the second transparent conductive layer.
[0009] By utilizing the above technical features, a composite photovoltaic structure can be obtained that can significantly improve the all-round light-concentrating gain photoelectric reaction area and effectively increase the amount of current without affecting the overall structure thickness and with low process cost.
[0010] According to the above technical features, the composite photovoltaic structure is provided with an optical hardening layer between the plate surface of the transparent substrate and the first transparent electrode layer and the second transparent electrode layer.
[0011] According to the above technical features, the first photovoltaic unit and the second photovoltaic unit are organic photovoltaic units.
[0012] According to the above technical features, the first photovoltaic unit and the second photovoltaic unit are perovskite photovoltaic units.
[0013] According to the above technical features, the first photovoltaic unit is an organic photovoltaic unit, and the second photovoltaic unit is a perovskite photovoltaic unit.
[0014] According to the above technical features, the first photovoltaic unit is a perovskite photovoltaic unit, and the second photovoltaic unit is an organic photovoltaic unit.
[0015] According to the above technical features, the first photovoltaic unit and the second photovoltaic unit are organic photovoltaic units; the transparent electron transfer layer of the first photovoltaic unit and the second photovoltaic unit can be formed by slit coating with PEI (polyethylenimine) and PEIE (polyethylenimine ethoxylated) as the main components and then drying with hot air at 90-140°C for 3 minutes, and the thickness is preferably 0.5-10nm; the transparent hole transfer layer of the first photovoltaic unit and the second photovoltaic unit can be solvent-diluted PEDOT:PSS (Poly (3,4-ethylenedioxythiophene)-poly (styrenesulfonate)) as the main component (PEDOT:PSS), including a polymer of a plurality of EDOT (3,4-ethylenedioxythiophene monomer) and a plurality of sodium polystyrene sulfonate (sodium-p-styrenesulfonate, P SS), such as diluted with a polar solvent such as alcohol (such as ethanol) and then slit coated and dried at 90-140°C in a nitrogen atmosphere for 5 minutes, and the thickness is preferably 100-500nm; the transparent active layer of the first photovoltaic unit and the second photovoltaic unit can be solvent-diluted P3HT / PCBM, PCPDTBT / PCBM (poly[2,6-(4,4-bis-(2-ethylhexyl)-4H-cyclopenta[2,1-b;3,4-b′]dithiophene)-alt-4,7-(2,1,3-benzothiadiazole)]:phenyl-C 61 -butyric acidmethyl ester), wherein P3HT / PCBM is a polymer semiconductor having multiple poly(3-hexylthiophene), P3HT (p-type material) and multiple phenyl-C 61 Methyl butyrate (phenyl-C 61-butyric acid methylester, PCBM (n-type material)), diluted with o-xylene, slit coated, and then dried at 90-140°C in a nitrogen atmosphere for 3 minutes to form a preferred thickness of 100-500nm.
[0016] According to the above technical features, the first photovoltaic unit and the second photovoltaic unit are perovskite photovoltaic units; the transparent electron transfer layer of the first photovoltaic unit and the second photovoltaic unit can be made of PEDOT:PSS, Poly (3-hexylthiophene) (P3HT) and
[0017] Poly(bis(4-phenyl)(2,4,6-trimethylphenyl)amine)(PTAA) is formed by slit coating and drying in a nitrogen atmosphere at 90-140°C for 5 minutes, and the thickness is preferably 100-500nm; the transparent hole transfer layer of the first photovoltaic unit and the second photovoltaic unit can be a main component containing PDPP3T:PCBM, which is diluted with a solvent and then dried in a nitrogen atmosphere at 90-140°C for 5 minutes after slit coating, and the thickness is preferably 1-100nm; the transparent active layer of the first photovoltaic unit and the second photovoltaic unit can be one of CH3NH3PbI3, CsPbBr3, CsPbI3, FAPbI3 (Formamidinium LeadIodide), FAPbBr3 (Formamidinium Lead Bromide) or a combination thereof, which is diluted with a solvent and then dried in a nitrogen atmosphere at 90-140°C for 5 minutes after slit coating, and the thickness is preferably 200-800nm.
[0018] According to the above technical features, the first photovoltaic unit is an organic photovoltaic unit, and the second photovoltaic unit is a perovskite photovoltaic unit; the transparent electron transfer layer of the first photovoltaic unit can be formed by slit coating with PEI and PEIE as the main components and then drying with hot air at 90-140°C for 3 minutes, and the thickness is preferably 0.5-10nm; the transparent hole transfer layer of the first photovoltaic unit can be a solvent-diluted PEDOT:PSS as the main component (PEDOT:PSS), including a polymer (PEDOT) of a plurality of EDOT (3,4-ethylenedioxythiophene monomer) and a plurality of sodium polystyrene sulfonates (sod The transparent active layer of the first photovoltaic unit can be P3HT / PCBM or PCPDTBT / PCBM diluted with solvent, wherein P3HT / PCBM is a polymer semiconductor having multiple poly(3-hexylthiophene, P3HT (p-type material)) and multiple phenyl-C 61 Methyl butyrate (phenyl-C 61 -butyric acidmethyl ester,PCBM (n-type material)), diluted with o-xylene, slit coated, and then dried at 90-140°C in a nitrogen atmosphere for 3 minutes to form a thickness of 100-500nm; the transparent electron transfer layer of the second photovoltaic unit can be made of PEDOT:PSS, Poly(3-hexylthiophene)(P3HT) and Poly(bis(4-phenyl)(2,4,6-trimethylphenyl)amine)(PTAA) slit coated, and then dried at 90-140°C in a nitrogen atmosphere for 5 minutes to form shape, and the thickness is preferably 100-500nm; the transparent hole transfer layer of the second photovoltaic unit can be a main component containing PDPP3T:PCBM, which is diluted with a solvent and then slit coated and dried in a nitrogen atmosphere at 90-140°C for 5 minutes to form a thickness of 1-100nm; the transparent active layer of the second photovoltaic unit can be one of CH3NH3PbI3, CsPbBr3, CsPbI3, FAPbI3, FAPbBr3 or a combination thereof, which is diluted with a solvent and then slit coated and dried in a nitrogen atmosphere at 90-140°C for 5 minutes to form a thickness of 200-800nm.
[0019] According to the above technical features, the first photovoltaic unit is a perovskite photovoltaic unit, and the second photovoltaic unit is an organic photovoltaic unit; the transparent electron transfer layer of the first photovoltaic unit can be composed of PEDOT:PSS, Poly (3-hexylthiophene) (P3HT) and
[0020] Poly(bis(4-phenyl)(2,4,6-trimethylphenyl)amine)(PTAA) is formed by drying at 90-140°C in a nitrogen atmosphere for 5 minutes after slit coating, and the thickness is preferably 100-500nm; the transparent hole transfer layer of the first photovoltaic unit can be a main component containing PDPP3T:PCBM, which is diluted with a solvent and then dried at 90-140°C in a nitrogen atmosphere for 5 minutes after slit coating, and the thickness is preferably 1-100nm; the transparent active layer of the first photovoltaic unit can be one of CH3NH3PbI3, CsPbBr3, CsPbI3, FAPbI3, FAPbBr3, or a combination thereof, which is diluted with a solvent and then dried at 90-140°C in a nitrogen atmosphere for 5 minutes after slit coating, and the thickness is preferably 200-800nm; the transparent electron transfer layer of the second photovoltaic unit can be a main component containing PEI or PEIE, which is diluted with a solvent and then dried at 90-140°C in a nitrogen atmosphere for 5 minutes after slit coating, and the thickness is preferably 200-800nm. The transparent hole transfer layer of the second photovoltaic unit can be a solvent-diluted PEDOT:PSS as the main component (PEDOT:PSS), comprising a polymer of a plurality of EDOT (3,4-ethylenedioxythiophene monomer) and a mixture of a plurality of sodium polystyrene sulfonate (sodium-p-styrenesulfonate, PSS), such as diluted with a polar solvent such as alcohol (such as ethanol) and then slit coated and dried in a nitrogen atmosphere at 90 to 140°C for 5 minutes, and the thickness is preferably 100 to 500 nm; the transparent active layer of the second photovoltaic unit can be a solvent-diluted P3HT / PCBM, PCPDTBT / PCBM, wherein P3HT / PCBM is a polymer semiconductor having a plurality of poly (3-hexylthiophene, P3HT (p-type material)) and a plurality of phenyl-C 61 Methyl butyrate (phenyl-C 61 -butyric acid methyl ester, PCBM (n-type material)), diluted with o-xylene, slit coated, and then dried at 90-140°C in a nitrogen atmosphere for 3 minutes to form a preferred thickness of 100-500nm.
[0021] According to the above technical features, the first transparent electrode layer and the second transparent electrode layer can be formed by evaporating or sputtering ITO (Indium Tin Oxide), IZO (Indium Doped Zinc Oxide) or AZO (Aluminum Doped Zinc Oxide) on the transparent substrate, and the thickness is preferably 50-200 nm.
[0022] According to the above technical features, the first transparent conductive layer is formed by evaporation of Ag, Au, Pt or Pd, and the thickness is preferably 50-200 nm.
[0023] According to the above technical features, the second transparent conductive layer is formed by evaporation of Ag, Au, Pt or Pd, and the thickness is preferably 50-200 nm.
[0024] According to the above technical features, the optical hardening layer can be one of acrylic, epoxy resin, silicon dioxide or a combination thereof, and the thickness is preferably 1 μm to 5 μm.
[0025] According to the above technical features, the first insulating layer and the second insulating layer can be made of polyester polymer by printing and coating and then drying under hot air at 90-140° C. for 10 minutes.
[0026] The composite photovoltaic structure manufacturing method of the present invention comprises the following steps: a. constructing a transparent electrode layer material, providing a transparent substrate, and setting a transparent electrode layer material with a preset thickness on the plate surface of the transparent substrate; b. constructing a first photovoltaic unit, sequentially constructing each layer of material of the first photovoltaic unit on the transparent electrode layer material, so that the upper surface layer and the lower surface layer of the first photovoltaic unit are respectively a transparent electron transfer layer and a transparent hole transfer layer, and a transparent active layer is provided between the upper surface layer and the lower surface layer of the first photovoltaic unit; c. constructing a first insulating layer, carving at least one first insulating material channel penetrating the transparent electrode layer material on the upper surface layer of the first photovoltaic unit, and at each of the first insulating material channels Filling insulating material in each of the first insulating material channels to form a first insulating layer in each of the first insulating material channels, and using each of the first insulating layers to separate the transparent electrode layer material into a first transparent electrode layer relatively located below the first photovoltaic unit and a second transparent electrode layer relatively located outside the first photovoltaic unit; d. constructing a first transparent conductive layer, carving a first transparent conductive material channel from the upper surface of the first photovoltaic unit to the transparent electrode layer material at the side position of each of the first insulating layers, and covering the upper surface of the first photovoltaic unit and each of the first transparent conductive material channels with transparent conductive material to form a channel covering the upper surface of the first photovoltaic unit and connecting the first photovoltaic unit with the second transparent electrode layer along the side of each of the first insulating layers. a transparent conductive layer electrically connected to a transparent electrode layer; e. constructing a second photovoltaic unit, sequentially constructing the materials of the second photovoltaic unit on the first transparent conductive layer on the top surface of the first photovoltaic unit, so that the upper surface layer and the lower surface layer of the second photovoltaic unit are respectively a transparent electron transfer layer and a transparent hole transfer layer, and a transparent active layer is provided between the upper surface layer and the lower surface layer of the second photovoltaic unit; f. constructing a second insulating layer, carving at least one second insulating material channel penetrating to the transparent electrode layer material on the upper surface layer of the second photovoltaic unit, and filling each second insulating material channel with insulating material, so that a second insulating layer is formed in each second insulating material channel; g. constructing a second transparent conductive layer h. Finished product segmentation, a cutting channel is cut on the surface of the second transparent conductive layer to penetrate to the transparent electrode layer material, and a composite photovoltaic structure is constructed on the transparent substrate to form at least one second photovoltaic unit stacked and connected in parallel with the first photovoltaic unit.
[0027] According to the above technical features, in the manufacturing method of the composite photovoltaic structure, an optical hardening layer is provided on the plate surface of the transparent substrate, and the transparent electrode layer material is provided on the optical hardening layer.
[0028] According to the above technical features, the first photovoltaic unit and the second photovoltaic unit are organic photovoltaic units.
[0029] According to the above technical features, the first photovoltaic unit and the second photovoltaic unit are perovskite photovoltaic units.
[0030] According to the above technical features, the first photovoltaic unit is an organic photovoltaic unit, and the second photovoltaic unit is a perovskite photovoltaic unit.
[0031] According to the above technical features, the first photovoltaic unit is a perovskite photovoltaic unit, and the second photovoltaic unit is an organic photovoltaic unit.
[0032] According to the above technical features, the first photovoltaic unit and the second photovoltaic unit are organic photovoltaic units; the transparent electron transfer layer of the first photovoltaic unit and the second photovoltaic unit can be formed by slit coating with PEI and PEIE as the main components and then drying with hot air at 90-140°C for 3 minutes, and the thickness is preferably 0.5-10nm; the transparent hole transfer layer of the first photovoltaic unit and the second photovoltaic unit can be a solvent-diluted PEDOT:PSS as the main component (PEDOT:PSS), including a polymer of a plurality of EDOT (3,4-ethylenedioxythiophene monomer) and a plurality of sodium polystyrene sulfonate (sodium- p-styrenesulfonate, PSS), such as diluted with alcohols and other polar solvents (such as ethanol) and then slit coated at 90-140 ° C in a nitrogen atmosphere for 5 minutes and then dried to form a thickness of 100-500nm; the transparent active layer of the first photovoltaic unit and the second photovoltaic unit can be solvent-diluted P3HT / PCBM, PCPDTBT / PCBM, wherein P3HT / PCBM is a polymer semiconductor with multiple poly (3-hexylthiophene, P3HT (p-type material)) and multiple phenyl-C 61 Methyl butyrate (phenyl-C 61 -butyric acid methylester, PCBM (n-type material)), diluted with o-xylene, slit coated, and then dried at 90-140°C in a nitrogen atmosphere for 3 minutes to form a preferred thickness of 100-500nm.
[0033] According to the above technical features, the first photovoltaic unit and the second photovoltaic unit are perovskite photovoltaic units; the transparent electron transfer layer of the first photovoltaic unit and the second photovoltaic unit can be made of PEDOT:PSS, Poly (3-hexylthiophene) (P3HT) and
[0034] Poly(bis(4-phenyl)(2,4,6-trimethylphenyl)amine)(PTAA) is formed by slit coating and drying at 90-140°C in a nitrogen atmosphere for 5 minutes, and the thickness is preferably 100-500nm; the transparent hole transfer layer of the first photovoltaic unit and the second photovoltaic unit can be a main component containing PDPP3T:PCBM, which is diluted with a solvent and then dried at 90-140°C in a nitrogen atmosphere for 5 minutes after slit coating, and the thickness is preferably 1-100nm; the transparent active layer of the first photovoltaic unit and the second photovoltaic unit can be one of CH3NH3PbI3, CsPbBr3, CsPbI3, FAPbI3, FAPbBr3 or a combination thereof, which is diluted with a solvent and then dried at 90-140°C in a nitrogen atmosphere for 5 minutes after slit coating, and the thickness is preferably 200-800nm.
[0035] According to the above technical features, the first photovoltaic unit is an organic photovoltaic unit, and the second photovoltaic unit is a perovskite photovoltaic unit; the transparent electron transfer layer of the first photovoltaic unit can be formed by slit coating with PEI and PEIE as the main components and then drying with hot air at 90-140°C for 3 minutes, and the thickness is preferably 0.5-10nm; the transparent hole transfer layer of the first photovoltaic unit can be a solvent-diluted PEDOT:PSS as the main component (PEDOT:PSS), including a plurality of EDOT (3,4-ethylenedioxythiophene monomer) polymers and a plurality of sodium polystyrene sulfonates (sodium- p-styrenesulfonate, PSS), such as diluted with alcohols and other polar solvents (such as ethanol) and then slit coated at 90-140 ° C in a nitrogen atmosphere for 5 minutes and then dried to form a thickness of 100-500nm; the transparent active layer of the first photovoltaic unit can be solvent-diluted P3HT / PCBM, PCPDTBT / PCBM, wherein P3HT / PCBM is a polymer semiconductor with multiple poly (3-hexylthiophene, P3HT (p-type material)) and multiple phenyl-C 61 Methyl butyrate (phenyl-C 61-butyric acidmethylester,PCBM (n-type material)), diluted with o-xylene, slit coated, and dried at 90-140°C in a nitrogen atmosphere for 3 minutes to form a thickness of 100-500nm; the transparent electron transfer layer of the second photovoltaic unit can be made of PEDOT:PSS, Poly (3-hexylthiophene) (P3HT) and
[0036] Poly(bis(4-phenyl)(2,4,6-trimethylphenyl)amine)(PTAA) is formed by slit coating and drying at 90-140°C in a nitrogen atmosphere for 5 minutes, and the thickness is preferably 100-500nm; the transparent hole transfer layer of the second photovoltaic unit can be a main component containing PDPP3T:PCBM, which is diluted with a solvent and then dried at 90-140°C in a nitrogen atmosphere for 5 minutes after slit coating, and the thickness is preferably 1-100nm; the transparent active layer of the second photovoltaic unit can be one of CH3NH3PbI3, CsPbBr3, CsPbI3, FAPbI3, FAPbBr3 or a combination thereof, which is diluted with a solvent and then dried at 90-140°C in a nitrogen atmosphere for 5 minutes after slit coating, and the thickness is preferably 200-800nm.
[0037] According to the above technical features, the first photovoltaic unit is a perovskite photovoltaic unit, and the second photovoltaic unit is an organic photovoltaic unit; the transparent electron transfer layer of the first photovoltaic unit can be composed of PEDOT:PSS, Poly (3-hexylthiophene) (P3HT) and
[0038] Poly(bis(4-phenyl)(2,4,6-trimethylphenyl)amine)(PTAA) is formed by drying at 90-140°C in a nitrogen atmosphere for 5 minutes after slit coating, and the thickness is preferably 100-500nm; the transparent hole transfer layer of the first photovoltaic unit can be a main component containing PDPP3T:PCBM, which is diluted with a solvent and then dried at 90-140°C in a nitrogen atmosphere for 5 minutes after slit coating, and the thickness is preferably 1-100nm; the transparent active layer of the first photovoltaic unit can be one of CH3NH3PbI3, CsPbBr3, CsPbI3, FAPbI3, FAPbBr3, or a combination thereof, which is diluted with a solvent and then dried at 90-140°C in a nitrogen atmosphere for 5 minutes after slit coating, and the thickness is preferably 200-800nm; the transparent electron transfer layer of the second photovoltaic unit can be a main component containing PEI or PEIE, which is diluted with a solvent and then dried at 90-140°C in a nitrogen atmosphere for 5 minutes after slit coating, and the thickness is preferably 200-800nm. The transparent hole transfer layer of the second photovoltaic unit can be a solvent-diluted PEDOT:PSS as the main component (PEDOT:PSS), comprising a polymer of a plurality of EDOT (3,4-ethylenedioxythiophene monomer) and a mixture of a plurality of sodium polystyrene sulfonate (sodium-p-styrenesulfonate, PSS), such as diluted with a polar solvent such as alcohol (such as ethanol) and then slit coated and dried in a nitrogen atmosphere at 90 to 140°C for 5 minutes, and the thickness is preferably 100 to 500 nm; the transparent active layer of the second photovoltaic unit can be a solvent-diluted P3HT / PCBM, PCPDTBT / PCBM, wherein P3HT / PCBM is a polymer semiconductor having a plurality of poly (3-hexylthiophene, P3HT (p-type material)) and a plurality of phenyl-C 61 Methyl butyrate (phenyl-C 61 -butyric acid methyl ester, PCBM (n-type material)), diluted with o-xylene, slit coated, and then dried at 90-140°C in a nitrogen atmosphere for 3 minutes to form a preferred thickness of 100-500nm.
[0039] According to the above technical features, the transparent electrode layer material can be made of ITO, IZO or AZO by evaporation or sputtering on the transparent substrate, and the thickness is preferably 50-200 nm.
[0040] According to the above technical features, the first transparent conductive layer is formed by evaporation of Ag, Au, Pt or Pd, and the thickness is preferably 50-200 nm.
[0041] According to the above technical features, the second transparent conductive layer is formed by evaporation of Ag, Au, Pt or Pd, and the thickness is preferably 50-200 nm.
[0042] According to the above technical features, the optical hardening layer can be one of acrylic, epoxy resin, silicon dioxide or a combination thereof, and the thickness is preferably 1 μm to 5 μm.
[0043] According to the above technical features, the first insulating layer and the second insulating layer can be made of polyester polymer by printing and coating and then drying under hot air at 90-140° C. for 10 minutes.
[0044] The composite photovoltaic structure disclosed in the present invention mainly utilizes the technical features of setting the first and second photovoltaic units stacked and connected in parallel on a transparent substrate. It can greatly improve the all-round focusing gain photoelectric reaction area without affecting the thickness of the overall structure, effectively increase the current, and not only has a low process cost, but also relatively meets the application requirements of small-volume products. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 FIG. 4 is a cross-sectional view of a conventional photovoltaic structure.
[0046] Figure 2 FIG. 4 is a cross-sectional view of a composite photovoltaic structure according to a first embodiment of the present invention.
[0047] Figure 3 FIG. 4 is a cross-sectional view of a composite photovoltaic structure according to a second embodiment of the present invention.
[0048] Figure 4 The basic flow chart of the composite photovoltaic structure manufacturing method of the present invention.
[0049] Figure 5 This is a diagram showing the completion of the transparent electrode layer material construction in the present invention.
[0050] Figure 6 This is a diagram showing the completion of the first photovoltaic unit construction in the present invention.
[0051] Figure 7 This is a diagram showing the completion of the first insulating layer of the present invention.
[0052] Figure 8 This is a diagram showing the completion of the construction of the first transparent conductive layer in the present invention.
[0053] Fig. 9 This is a diagram showing the completion of the second photovoltaic unit construction in the present invention.
[0054] Fig.10 This is a diagram showing the completion of the second insulating layer construction in the present invention.
[0055] Fig.11 This is a diagram showing the completion of the construction of the second transparent conductive layer in the present invention.
[0056] Fig.12 This is a diagram showing the completion of segmentation of the first transparent electrode layer and the second transparent electrode layer in the present invention.
[0057] Description of the figure number:
[0058] Prior Art
[0059] 11 Transparent substrate
[0060] 12 Photovoltaic units
[0061] 121 Lower surface
[0062] 122 Transparent Active Layer
[0063] 123 Upper surface
[0064] 131 first transparent electrode layer
[0065] 132 second transparent electrode layer
[0066] 141 transparent conductive layer
[0067] 142 insulation layer
[0068] The present invention
[0069] 20 transparent substrate
[0070] 21 First insulating material channel
[0071] 22. First transparent conductive material channel
[0072] 23 Second insulating material channel
[0073] 24 Second transparent conductive material channel
[0074] 25 Cutting Channels
[0075] 30 First photovoltaic unit
[0076] 31 Lower surface
[0077] 32 Transparent Active Layer
[0078] 33 Upper surface
[0079] 40 Second photovoltaic unit
[0080] 41 Lower surface
[0081] 42 Transparent Active Layer
[0082] 43 Upper surface
[0083] 50 Transparent electrode layer material
[0084] 51 first transparent electrode layer
[0085] 52 second transparent electrode layer
[0086] 61 first transparent conductive layer
[0087] 62 second transparent conductive layer
[0088] 71 First insulation layer
[0089] 72 Second insulation layer
[0090] 80 Optically hardened layer. DETAILED DESCRIPTION
[0091] The present invention mainly provides a composite photovoltaic structure which can greatly improve the all-round light-gathering gain photoelectric reaction area, effectively increase the current, does not affect the thickness of the overall structure, and has a low process cost, such as Figure 2 As shown, the composite photovoltaic structure of the present invention has a first photovoltaic unit 30 on a transparent substrate 20, and a second photovoltaic unit 40 connected in parallel with the first photovoltaic unit 30 is stacked on the first photovoltaic unit 30; the upper surface layer 33, 43 and the lower surface layer 31, 41 of the first photovoltaic unit 30 and the second photovoltaic unit 40 are respectively a transparent electron transfer layer and a transparent hole transfer layer, and the first photovoltaic unit 30 and the second photovoltaic unit 40 each have a transparent active layer 32, 42 between their upper surface layer 33, 43 and lower surface layer 31, 41.
[0092] A first transparent electrode layer 51 and a second transparent electrode layer 52 are provided on the surface of the transparent substrate 20 to form an insulated and separated relationship. The first photovoltaic unit 30 is provided on the second transparent electrode layer 52 in a state where its lower surface layer 31 contacts the second transparent electrode layer 52. A first transparent conductive layer 61 electrically connected to the first transparent electrode layer 51 is covered on the upper surface layer 33 of the first photovoltaic unit 30.
[0093] The second photovoltaic unit 40 is disposed on the first transparent conductive layer 61 with its lower surface 41 in contact with the first transparent conductive layer 61 ; the upper surface 43 of the second photovoltaic unit 40 is covered with a second transparent conductive layer 62 electrically connected to the second transparent electrode layer 52 .
[0094] Furthermore, the first transparent conductive layer 61 extends along the side of the first photovoltaic unit 30 to the first transparent electrode layer 51, and a first insulating layer 71 is provided between the side of the first photovoltaic unit 30 and the first transparent conductive layer 61; the second transparent conductive layer 62 extends along the side of the second photovoltaic unit 40, the side of the first transparent conductive layer 61 and the side of the first photovoltaic unit 30 to the second transparent electrode layer 52, and a second insulating layer 72 is provided between the side of the second photovoltaic unit 40, the side of the first transparent conductive layer 61, the side of the first photovoltaic unit 30 and the second transparent conductive layer 62.
[0095] In principle, in practical applications, the composite photovoltaic structure of the present invention can be connected in series with different numbers of composite photovoltaic structures to form a photovoltaic cell group, and ALD (atomic layer deposition) spraying is used to form aluminum oxide or silicon dioxide for deposition barrier to achieve air barrier packaging, or transparent packaging materials such as glass substrates or transparent plastic plates are used to complete air barrier packaging, that is, the design of setting the first and second photovoltaic units 30 and 40 stacked and connected in parallel on the transparent substrate 20 can be used to greatly improve the all-round focusing gain photoelectric reaction area without affecting the thickness of the overall structure, effectively increase the current, not only with low process cost, but also relatively meet the application requirements of small-volume products. The transparent substrate 20 can be transparent glass or a transparent plastic film, such as a transparent PET (polyester) film.
[0096] Furthermore, the composite photovoltaic structure of the present invention can be Figure 3 As shown, an optical hardening layer 80 is further provided between the plate surface of the transparent substrate 20 and the first transparent electrode layer 51 and the second transparent electrode layer 52; during implementation, the optical hardening layer 80 can be one of acrylic, epoxy resin, silicon dioxide or a combination thereof, and the thickness is preferably 1μm to 5μm. The provision of the optical hardening layer 80 can be used to increase the mechanical structural strength of the overall composite photovoltaic structure.
[0097] The composite photovoltaic structure of the present invention, when implemented, can be presented in an implementation state in which the first photovoltaic unit 30 and the second photovoltaic unit 40 are organic photovoltaic units; or in an implementation state in which the first photovoltaic unit 30 and the second photovoltaic unit 40 are perovskite photovoltaic units; or in an implementation state in which the first photovoltaic unit 30 is an organic photovoltaic unit and the second photovoltaic unit 40 is a perovskite photovoltaic unit; or in an implementation state in which the first photovoltaic unit 30 is a perovskite photovoltaic unit and the second photovoltaic unit 40 is an organic photovoltaic unit.
[0098] As for whether the upper surface layers 31 and 41 of the first photovoltaic unit 30 and the second photovoltaic unit 40 are transparent electron transfer layers or transparent hole transfer layers respectively, corresponding adjustments can be made according to the actual electrode configuration.
[0099] The composite photovoltaic structure of the present invention, in the embodiment of the first photovoltaic unit 30 and the second photovoltaic unit 40 being organic photovoltaic units; the transparent electron transfer layer of the first photovoltaic unit 30 and the second photovoltaic unit 40 can be formed by slit coating with PEI or PEIE as the main component and then drying with hot air at 90-140°C for 3 minutes, and the thickness is preferably 0.5-10nm; the transparent hole transfer layer of the first photovoltaic unit 30 and the second photovoltaic unit 40 can be a solvent-diluted PEDOT:PSS as the main component (that is, a mixture of PEDOT and PSS), including a plurality of EDOT (3,4-ethylenedioxythiophene monomer) polymers and a plurality of sodium polystyrene sulfonates (sodium-p-st The transparent active layers 32 and 42 of the first photovoltaic unit 30 and the second photovoltaic unit 40 can be solvent-diluted P3HT / PCBM (mixed with P3HT and PCBM) or PCPDTBT / PCBM (mixed with PCPDTBT and PCBM), wherein P3HT / PCBM is a polymer semiconductor having a plurality of poly(3-hexylthiophene), P3HT (p-type material) and a plurality of phenyl-C 61 Methyl butyrate (phenyl-C 61 -butyric acid methyl ester, PCBM (n-type material)), diluted with o-xylene, slit coated, and then dried at 90-140°C in a nitrogen atmosphere for 3 minutes to form a preferred thickness of 100-500nm.
[0100] In the composite photovoltaic structure of the present invention, in the embodiment where the first photovoltaic unit 30 and the second photovoltaic unit 40 are perovskite photovoltaic units; the transparent electron transfer layer of the first photovoltaic unit 30 and the second photovoltaic unit 40 can be made of PEDOT:PSS (PEDOT and PSS mixture), Poly (3-hexylthiophene) (P3HT) or
[0101] Poly(bis(4-phenyl)(2,4,6-trimethylphenyl)amine)(PTAA) is formed by slit coating and drying in a nitrogen atmosphere at 90-140°C for 5 minutes, and the thickness is preferably 100-500nm; the transparent hole transfer layer of the first photovoltaic unit 30 and the second photovoltaic unit 40 can be a main component containing PDPP3T:PCBM (a mixture of PDPP3T and PCBM) and is diluted with a solvent and then dried in a nitrogen atmosphere at 90-140°C for 5 minutes, and the thickness is preferably 1-100nm; the transparent active layers 32 and 42 of the first photovoltaic unit 30 and the second photovoltaic unit (40) can be one of CH3NH3PbI3, CsPbBr3, CsPbI3, FAPbI3, FAPbBr3 or a combination thereof, and is diluted with a solvent and then dried in a nitrogen atmosphere at 90-140°C for 5 minutes, and the thickness is preferably 200-800nm.
[0102] The composite photovoltaic structure of the present invention, in the embodiment in which the first photovoltaic unit 30 is an organic photovoltaic unit and the second photovoltaic unit 40 is a perovskite photovoltaic unit; the transparent electron transfer layer of the first photovoltaic unit 30 can be formed by slit coating with PEI or PEIE as the main component and then drying with hot air at 90-140°C for 3 minutes, and the thickness is preferably 0.5-10nm; the transparent hole transfer layer of the first photovoltaic unit 30 can be a solvent-diluted PEDOT:PSS as the main component (PEDOT:PSS), including a polymer of a plurality of EDOT (3,4-ethylenedioxythiophene monomer) and a plurality of sodium polystyrene sulfonates ( The transparent active layer 32 of the first photovoltaic unit 30 can be a solvent-diluted P3HT / PCBM, PCPDTBT / PCBM, wherein P3HT / PCBM is a polymer semiconductor having a plurality of poly(3-hexylthiophene), P3HT (p-type material) and a plurality of phenyl-C 61 Methyl butyrate (phenyl-C 61 -butyric acid methyl ester, PCBM (n-type material)), diluted with o-xylene, slit coated, and then dried at 90-140°C in a nitrogen atmosphere for 3 minutes to form a thickness of 100-500nm; the transparent electron transfer layer of the second photovoltaic unit 40 can be made of PEDOT:PSS, Poly (3-hexylthiophene) (P3HT) or
[0103] Poly(bis(4-phenyl)(2,4,6-trimethylphenyl)amine)(PTAA) is formed by slit coating and drying at 90-140°C in a nitrogen atmosphere for 5 minutes, and the thickness is preferably 100-500nm; the transparent hole transfer layer of the second photovoltaic unit 40 can be a main component containing PDPP3T:PCBM (a mixture of PDPP3T and PCBM), which is diluted with a solvent and then dried at 90-140°C in a nitrogen atmosphere for 5 minutes after slit coating, and the thickness is preferably 1-100nm; the transparent active layer 42 of the second photovoltaic unit 40 can be one of CH3NH3PbI3, CsPbBr3, CsPbI3, FAPbI3, FAPbBr3, or a combination thereof, which is diluted with a solvent and then dried at 90-140°C in a nitrogen atmosphere for 5 minutes after slit coating, and the thickness is preferably 200-800nm.
[0104] In the composite photovoltaic structure of the present invention, in the embodiment in which the first photovoltaic unit 30 is a perovskite photovoltaic unit and the second photovoltaic unit 40 is an organic photovoltaic unit; the transparent electron transfer layer of the first photovoltaic unit 30 can be formed by slit coating of PEDOT:PSS, Poly(3-hexylthiophene)(P3HT) or Poly(bis(4-phenyl)(2,4,6-trimethylphenyl)amine)(PTAA) and drying for 5 minutes at 90-140°C in a nitrogen atmosphere, and the thickness is Preferably, the thickness is 100 to 500 nm; the transparent hole transfer layer of the first photovoltaic unit 30 can be a main component containing PDPP3T:PCBM, which is diluted with a solvent and then slit coated and dried in a nitrogen atmosphere at 90 to 140°C for 5 minutes to form a shape, and the thickness is preferably 1 to 100 nm; the transparent active layer 32 of the first photovoltaic unit 30 can be one of CH3NH3PbI3, CsPbBr3, CsPbI3, FAPbI3, FAPbBr3 or a combination thereof, which is diluted with a solvent and then slit coated and dried in a nitrogen atmosphere at 90 to 140°C for 5 minutes to form a shape. The transparent electron transfer layer of the second photovoltaic unit 40 can be formed by PEI and PEIE as the main components through slit coating and then hot air drying at 90-140°C for 3 minutes, and the thickness is preferably 0.5-10nm; the transparent hole transfer layer of the second photovoltaic unit 40 can be a solvent-diluted PEDOT:PSS as the main component (PEDOT:PSS), including a plurality of EDOT (3,4-ethylenedioxythiophene monomer) polymers and a plurality of sodium polystyrene sulfonates (sodium-p-styrenesu lfonate, PSS), such as diluted with alcohols and other polar solvents (such as ethanol) and then slit coated at 90-140 ° C in a nitrogen atmosphere for 5 minutes and then dried to form a thickness of 100-500nm; the transparent active layer 42 of the second photovoltaic unit 40 can be solvent-diluted P3HT / PCBM, PCPDTBT / PCBM, wherein P3HT / PCBM is a polymer semiconductor with multiple poly (3-hexylthiophene, P3HT (p-type material)) and multiple phenyl-C 61 Methyl butyrate (phenyl-C 61 -butyric acid methyl ester, PCBM (n-type material), diluted with o-xylene, slit coated, and dried at 90-140°C in a nitrogen atmosphere for 3 minutes to form a preferred thickness of 100-500nm.
[0105] In the implementation of the composite photovoltaic structure of the present invention, the first transparent electrode layer 51 and the second transparent electrode layer 52 can be formed by evaporation or sputtering of ITO, IZO or AZO on the transparent substrate 20 , and the thickness is preferably 50-200 nm.
[0106] In the implementation of the composite photovoltaic structure of the present invention, the first transparent conductive layer 61 is formed by evaporation of Ag, Au, Pt or Pd, and the thickness is preferably 50-200 nm.
[0107] In the implementation of the composite photovoltaic structure of the present invention, the second transparent conductive layer 62 is formed by evaporation of Ag, Au, Pt or Pd, and the thickness is preferably 50-200 nm.
[0108] In the implementation of the composite photovoltaic structure of the present invention, the first insulating layer 71 and the second insulating layer 72 can be made of polyester polymer by printing and coating and then drying under hot air at 90-140° C. for 10 minutes.
[0109] The present invention further discloses a method for manufacturing a composite photovoltaic structure, such as Figures 4 to 12 As shown, the method for manufacturing the composite photovoltaic structure of the present invention comprises the following steps.
[0110] a. Building a transparent electrode layer material 50 , providing a transparent substrate 20 , and disposing a transparent electrode layer material 50 with a preset thickness on the surface of the transparent substrate 20 .
[0111] b. Construct the first photovoltaic unit 30, and construct the various layers of materials of the first photovoltaic unit 30 in sequence on the transparent electrode layer material 50. The upper surface layer 33 and the lower surface layer 31 of the first photovoltaic unit 30 are respectively a transparent electron transfer layer and a transparent hole transfer layer, and a transparent active layer 32 is provided between the upper surface layer 33 and the lower surface layer 31 of the first photovoltaic unit 30.
[0112] c. constructing a first insulating layer 71, and using a scribing means to scribble at least one first insulating material channel 21 penetrating the transparent electrode layer material 50 on the upper surface of the first photovoltaic unit 30, and filling each of the first insulating material channels 21 with insulating material, so that a first insulating layer 71 is formed in each of the first insulating material channels 21, and each of the first insulating layers 71 separates the transparent electrode layer material 50 into a first transparent electrode layer 51 relatively located below the first photovoltaic unit 30 and a second transparent electrode layer 52 relatively located outside the first photovoltaic unit 30. The scribing means is etched by laser, for example, etching is performed by laser on the upper surface of the first photovoltaic unit 30 to scribble at least one first insulating material channel 21 penetrating the transparent electrode layer material 50.
[0113] d. constructing a first transparent conductive layer 61, and using the scribing means to scribble out a first transparent conductive material channel 22 from the upper surface layer 33 of the first photovoltaic unit 30 to the transparent electrode layer material 50 at the side position of each first insulating layer 71, and coating the surface of the upper surface layer 33 of the first photovoltaic unit 30 and each of the first transparent conductive material channels 22 with transparent conductive material, so as to form a first transparent conductive layer 61 that covers the upper surface of the first photovoltaic unit 30 and is electrically connected to the first transparent electrode layer 51 along the side of each first insulating layer 71.
[0114] e. Construct a second photovoltaic unit 40, and construct the various layers of materials of the second photovoltaic unit 40 in sequence on the first transparent conductive layer 61 on the top surface of the first photovoltaic unit 30, the upper surface layer 43 and the lower surface layer 41 of the second photovoltaic unit 40 are respectively a transparent electron transfer layer and a transparent hole transfer layer, and a transparent active layer 42 is provided between the upper surface layer 43 and the lower surface layer 41 of the second photovoltaic unit 40.
[0115] f. construct a second insulating layer 72, and use the scribing means to carve at least one second insulating material channel 23 that penetrates the transparent electrode layer material 50 on the upper surface layer 43 of the second photovoltaic unit 40, and fill each of the second insulating material channels 23 with insulating material to form a second insulating layer 72 in each of the second insulating material channels 23.
[0116] g. construct a second transparent conductive layer 62, and use the scribing means to scratch out second transparent conductive material channels 24 from the upper surface layer 43 of the second photovoltaic unit 40 to the transparent electrode layer material 50 at the side position of each second insulating layer 72, and cover the surface of the upper surface layer 43 of the second photovoltaic unit 40 and each of the second transparent conductive material channels 24 with transparent conductive material, so as to form a second transparent conductive layer 62 that covers the upper surface layer 43 of the second photovoltaic unit 40 and is electrically connected to the second transparent electrode layer 52 along the side of each second insulating layer 72.
[0117] h. Finished product segmentation, the cutting channel 25 penetrating to the transparent electrode layer material 50 is segmented on the surface of the second transparent conductive layer 62 by the segmentation means, thereby segmenting the composite photovoltaic structure (such as Figure 2 shown).
[0118] Similarly, when the composite photovoltaic structure manufacturing method of the present invention is implemented, an optical hardening layer 80 (such as Figure 3As shown), the transparent electrode layer material 50 is disposed on the optical hardening layer 80; during implementation, the optical hardening layer 80 can be one of acrylic, epoxy resin, silicon dioxide or a combination thereof, and the thickness is preferably 1μm to 5μm. The optical hardening layer 80 is used to increase the mechanical structural strength of the overall composite photovoltaic structure.
[0119] The composite photovoltaic structure manufacturing method of the present invention, when implemented, can be presented in an implementation state in which the first photovoltaic unit 30 and the second photovoltaic unit 40 are organic photovoltaic units; or in an implementation state in which the first photovoltaic unit 30 and the second photovoltaic unit 40 are perovskite photovoltaic units; or in an implementation state in which the first photovoltaic unit 30 is an organic photovoltaic unit and the second photovoltaic unit 40 is a perovskite photovoltaic unit; or in an implementation state in which the first photovoltaic unit 30 is a perovskite photovoltaic unit and the second photovoltaic unit 40 is an organic photovoltaic unit.
[0120] The composite photovoltaic structure manufacturing method of the present invention, in the embodiment of the first photovoltaic unit 30 and the second photovoltaic unit 40 being organic photovoltaic units; the transparent electron transfer layer of the first photovoltaic unit 30 and the second photovoltaic unit 40 can be formed by slit coating with PEI and PEIE as the main components and then drying with hot air at 90-140°C for 3 minutes, and the thickness is preferably 0.5-10nm; the transparent hole transfer layer of the first photovoltaic unit 30 and the second photovoltaic unit 40 can be a solvent-diluted PEDOT:PSS as the main component (PEDOT:PSS), including a polymer of a plurality of EDOT (3,4-ethylenedioxythiophene monomer) and a plurality of sodium polystyrene sulfonates ( The transparent active layers 32 and 42 of the first photovoltaic unit (30) and the second photovoltaic unit 40 can be P3HT / PCBM or PCPDTBT / PCBM diluted with solvent, wherein P3HT / PCBM is a polymer semiconductor having a plurality of poly(3-hexylthiophene), P3HT (p-type material) and a plurality of phenyl-C 61 Methyl butyrate (phenyl-C 61 -butyric acid methyl ester, PCBM (n-type material)), diluted with o-xylene, slit coated, and then dried at 90-140°C in a nitrogen atmosphere for 3 minutes to form a preferred thickness of 100-500nm.
[0121] The composite photovoltaic structure manufacturing method of the present invention, in the embodiment of the first photovoltaic unit 30 and the second photovoltaic unit 40 are perovskite photovoltaic units; the transparent electron transfer layer of the first photovoltaic unit 30 and the second photovoltaic unit 40 can be made of PEDOT:PSS, Poly (3-hexylthiophene) (P3HT) or
[0122] Poly(bis(4-phenyl)(2,4,6-trimethylphenyl)amine)(PTAA) is formed by slit coating and drying in a nitrogen atmosphere at 90-140°C for 5 minutes, and the thickness is preferably 100-500nm; the transparent hole transfer layer of the first photovoltaic unit 30 and the second photovoltaic unit 40 can be a main component containing PDPP3T:PCBM, which is diluted with a solvent and then dried in a nitrogen atmosphere at 90-140°C for 5 minutes after slit coating, and the thickness is preferably 1-100nm; the transparent active layers 32 and 42 of the first photovoltaic unit (30) and the second photovoltaic unit 40 can be one of CH3NH3PbI3, CsPbBr3, CsPbI3, FAPbI3, FAPbBr3 or a combination thereof, which is diluted with a solvent and then dried in a nitrogen atmosphere at 90-140°C for 5 minutes after slit coating, and the thickness is preferably 200-800nm.
[0123] The composite photovoltaic structure manufacturing method of the present invention is implemented in the state that the first photovoltaic unit 30 is an organic photovoltaic unit and the second photovoltaic unit 40 is a perovskite photovoltaic unit; the transparent electron transfer layer of the first photovoltaic unit 30 can be formed by PEI or PEIE as the main component after slit coating and hot air drying at 90-140°C for 3 minutes, and the thickness is preferably 0.5-10nm; the transparent hole transfer layer of the first photovoltaic unit 30 can be a solvent-diluted PEDOT:PSS as the main component (PEDOT:PSS), including a plurality of EDOT (3,4-ethylenedioxythiophene monomer) polymers and a plurality of sodium polystyrene sulfonates (sodium-p-st yrenesulfonate, PSS), such as diluted with alcohols and other polar solvents (such as ethanol) and then slit coated at 90 ~ 140 ℃ nitrogen atmosphere for 5 minutes after drying to form a thickness of 100 ~ 500nm; the transparent active layer 32 of the first photovoltaic unit 30 can be solvent-diluted P3HT / PCBM, PCPDTBT / PCBM, wherein P3HT / PCBM has a plurality of poly 3-hexylthiophene (poly (3-hexylthiophene, P3HT (p-type material)) polymer semiconductor and a plurality of phenyl-C61-butyric acid methyl ester (phenyl-C61-butyric acid methyl ester) acid methyl ester, PCBM (n-type material), diluted with o-xylene, slit coated, and dried at 90-140°C in a nitrogen atmosphere for 3 minutes to form a thickness of 100-500nm; the transparent electron transfer layer of the second photovoltaic unit 40 can be made of PEDOT:PSS, Poly (3-hexylthiophene) (P3HT) or
[0124] Poly(bis(4-phenyl)(2,4,6-trimethylphenyl)amine)(PTAA) is formed by slit coating and drying at 90-140°C in a nitrogen atmosphere for 5 minutes, and the thickness is preferably 100-500nm; the transparent hole transfer layer of the second photovoltaic unit 40 can be a main component containing PDPP3T:PCBM, which is diluted with a solvent and then dried at 90-140°C in a nitrogen atmosphere for 5 minutes after slit coating, and the thickness is preferably 1-100nm; the transparent active layer 42 of the second photovoltaic unit 40 can be one of CH3NH3PbI3, CsPbBr3, CsPbI3, FAPbI3, FAPbBr3 or a combination thereof, which is diluted with a solvent and then dried at 90-140°C in a nitrogen atmosphere for 5 minutes after slit coating, and the thickness is preferably 200-800nm.
[0125] In the composite photovoltaic structure manufacturing method of the present invention, in the embodiment in which the first photovoltaic unit 30 is a perovskite photovoltaic unit and the second photovoltaic unit 40 is an organic photovoltaic unit, the transparent electron transfer layer of the first photovoltaic unit 30 can be formed by slit coating, followed by drying at 90-140° C. in a nitrogen atmosphere for 5 minutes. The thickness is preferably 100 to 500 nm; the transparent hole transfer layer of the first photovoltaic unit 30 can be a main component containing PDPP3T:PCBM, which is diluted with a solvent and then slit coated and dried in a nitrogen atmosphere at 90 to 140°C for 5 minutes, and the thickness is preferably 1 to 100 nm; the transparent active layer (32) of the first photovoltaic unit 30 can be one of CH3NH3PbI3, CsPbBr3, CsPbI3, FAPbI3, FAPbBr3 or a combination thereof, which is diluted with a solvent and then slit coated and dried in a nitrogen atmosphere at 90 to 140°C for 5 minutes The transparent electron transfer layer of the second photovoltaic unit 40 can be formed by slit coating with PEI and PEIE as the main components and then drying with hot air at 90-140°C for 3 minutes, and the thickness is preferably 0.5-10nm; the transparent hole transfer layer of the second photovoltaic unit 40 can be mainly composed of PEDOT:PSS diluted by solvent (PEDOT:PSS), including a polymer of multiple EDOT (3,4-ethylenedioxythiophene monomer) and multiple sodium polystyrene sulfonate (sodium-p-styrene sulfonate, PSS), such as diluted with alcohols and other polar solvents (such as ethanol) and then slit coated at 90-140 ° C in a nitrogen atmosphere for 5 minutes and then dried to form a thickness of 100-500 nm; the transparent active layer 42 of the second photovoltaic unit 40 can be solvent-diluted P3HT / PCBM, PCPDTBT / PCBM, wherein P3HT / PCBM is a polymer semiconductor with multiple poly (3-hexylthiophene, P3HT (p-type material)) and multiple phenyl-C 61 Methyl butyrate (phenyl-C 61 -butyric acid methyl ester, PCBM (n-type material), diluted with o-xylene, slit coated, and dried at 90-140°C in a nitrogen atmosphere for 3 minutes to form a preferred thickness of 100-500nm.
[0126] When the composite photovoltaic structure manufacturing method of the present invention is implemented, the transparent electrode layer material 50 can be made of ITO, IZO or AZO by evaporation or sputtering on the transparent substrate 20, and the thickness is preferably 50-200 nm.
[0127] In the method for manufacturing the composite photovoltaic structure of the present invention, when the first transparent conductive layer 61 is formed by evaporation of Ag, Au, Pt or Pd, the thickness of which is preferably 50-200 nm.
[0128] In the implementation of the composite photovoltaic structure manufacturing method of the present invention, the second transparent conductive layer 62 is formed by evaporation of Ag, Au, Pt or Pd, and the thickness is preferably 50-200 nm.
[0129] In the composite photovoltaic structure manufacturing method of the present invention, when being implemented, the first insulating layer (71) and the second insulating layer 72 can be made of polyester polymer by printing and coating and then drying under hot air at 90-140° C. for 10 minutes.
[0130] Examples 1 to 3, Comparative Example 1 and test results. Using the aforementioned composite photovoltaic structure and composite photovoltaic structure manufacturing method, 10 corresponding composite photovoltaic structures (length 2.5 cm, width 0.5 cm) of Examples 1 to 3 were respectively manufactured to form a photovoltaic battery assembly formed by connecting in series; another 10 composite photovoltaic structures (length 2.5 cm, width 0.5 cm) of the prior art were used to manufacture a photovoltaic battery assembly formed by connecting in series. Figure 1 The structure of the comparative example 1 shown in the figure is connected in series to form a photovoltaic battery group. After the battery group is encapsulated with a gas barrier film, it is placed on both sides / surfaces of the substrate and illuminated by a light source, providing an illumination environment of 1000 lux. The open circuit voltage (V) can be measured and the short circuit current per unit area (I / cm 2 ). The test results are shown in Table 1.
[0131] Table 1.
[0132]
[0133]
[0134] In Example 1, the first photovoltaic unit 30 and the second photovoltaic unit 40 are organic photovoltaic units; in Example 2, the first photovoltaic unit 30 and the second photovoltaic unit 40 are perovskite photovoltaic units; in Example 3, the first photovoltaic unit 30 is an organic photovoltaic unit, and the second photovoltaic unit 40 is a perovskite photovoltaic unit. In Comparative Example 1, a conventional photovoltaic structure using an organic photovoltaic unit is used. Obviously, the open circuit voltage and the short circuit current per unit area of Examples 1 to 3 of the composite photovoltaic structure of the present invention are better than those of Comparative Example 1 of the conventional photovoltaic structure.
[0135] Specifically, the composite photovoltaic structure disclosed in the present invention mainly utilizes the technical features of setting the first and second photovoltaic units stacked and connected in parallel on a transparent substrate. It can greatly improve the all-round focusing gain photoelectric reaction area without affecting the thickness of the overall structure, effectively increase the current, and not only has a low process cost, but also relatively meets the application requirements of small-volume products.
Claims
1. A composite photovoltaic structure, characterized in that: A first photovoltaic unit (30) is provided on a transparent substrate (20), and a second photovoltaic unit (40) connected in parallel with the first photovoltaic unit (30) is stacked on the first photovoltaic unit (30); an upper surface layer (33), (43) and a lower surface layer (31), (41) of the first photovoltaic unit (30) and the second photovoltaic unit (40) are respectively a transparent electron transfer layer and a transparent hole transfer layer; the first photovoltaic unit (30) and the second photovoltaic unit (40) are each provided with a transparent active layer (32), (42) between the upper surface layer (33), (43) and the lower surface layer (31), (41); wherein: A first transparent electrode layer (51) and a second transparent electrode layer (52) are provided on the surface of the transparent substrate (20) so as to be insulated and separated from each other. The first photovoltaic unit (30) is provided on the second transparent electrode layer (52) in a state where its lower surface layer (31) contacts the second transparent electrode layer (52); a first transparent conductive layer (61) electrically connected to the first transparent electrode layer (51) is provided on the upper surface layer (33) of the first photovoltaic unit (30); the second photovoltaic unit (40) is provided on the first transparent conductive layer (61) in a state where its lower surface layer (41) contacts the first transparent conductive layer (61); a first transparent conductive layer (61) electrically connected to the second transparent electrode layer (51) is provided on the upper surface layer (43) of the second photovoltaic unit (40). The invention relates to a second transparent conductive layer (62) electrically connected to the first photovoltaic unit (30); the first transparent conductive layer (61) extends along the side of the first photovoltaic unit (30) to the first transparent electrode layer (51), and a first insulating layer (71) is provided between the side of the first photovoltaic unit (30) and the first transparent conductive layer (61); the second transparent conductive layer (62) extends along the side of the second photovoltaic unit (40), the side of the first transparent conductive layer (61) and the side of the first photovoltaic unit (30) to the second transparent electrode layer (52), and a second insulating layer (72) is provided between the side of the second photovoltaic unit (40), the side of the first transparent conductive layer (61) and the side of the first photovoltaic unit (30) and the second transparent conductive layer (62).
2. The composite photovoltaic structure according to claim 1, characterized in that: The composite photovoltaic structure is provided with an optical hardening layer (80) between the plate surface of the transparent substrate (20) and the first transparent electrode layer (51) and the second transparent electrode layer (52).
3. The composite photovoltaic structure according to claim 1 or 2, characterized in that: The first photovoltaic unit (30) and the second photovoltaic unit (40) are organic photovoltaic units.
4. The composite photovoltaic structure according to claim 1 or 2, characterized in that: The first photovoltaic unit (30) and the second photovoltaic unit (40) are perovskite photovoltaic units.
5. The composite photovoltaic structure according to claim 1 or 2, characterized in that: The first photovoltaic unit (30) is an organic photovoltaic unit, and the second photovoltaic unit (40) is a perovskite photovoltaic unit.
6. The composite photovoltaic structure according to claim 1 or 2, characterized in that: The first photovoltaic unit (30) is a perovskite photovoltaic unit, and the second photovoltaic unit (40) is an organic photovoltaic unit.
7. The composite photovoltaic structure according to claim 1 or 2, characterized in that: The first photovoltaic unit (30) and the second photovoltaic unit (40) are organic photovoltaic units; the transparent electron transfer layer of the first photovoltaic unit (30) and the second photovoltaic unit (40) is PEI or PEIE, with a thickness of 0.5 to 10 nm; the transparent hole transfer layer of the first photovoltaic unit (30) and the second photovoltaic unit (40) is a mixture of PEDOT and PSS, with a thickness of 100 to 500 nm; the transparent active layers (32) and (42) of the first photovoltaic unit (30) and the second photovoltaic unit (40) are a mixture of P3HT and PCBM or a mixture of PCPDTBT and PCBM, with a thickness of 100 to 500 nm.
8. The composite photovoltaic structure according to claim 1 or 2, characterized in that: The first photovoltaic unit (30) and the second photovoltaic unit (40) are perovskite photovoltaic units; the transparent electron transfer layer of the first photovoltaic unit (30) and the second photovoltaic unit (40) is composed of a mixture of PEDOT and PSS or of P3HT or PTAA, and has a thickness of 100 to 500 nm; the transparent hole transfer layer of the first photovoltaic unit (30) and the second photovoltaic unit (40) is composed of a mixture of PDPP3T and PCBM, and has a thickness of 1 to 100 nm; the transparent active layers (32) and (42) of the first photovoltaic unit (30) and the second photovoltaic unit (40) are composed of a mixture of one of CH3NH3PbI3, CsPbBr3, CsPbI3, FAPbI3, FAPbBr3 or a combination thereof, and have a thickness of 200 to 800 nm.
9. The composite photovoltaic structure according to claim 1 or 2, characterized in that: The first photovoltaic unit (30) is an organic photovoltaic unit, and the second photovoltaic unit (40) is a perovskite photovoltaic unit; the transparent electron transfer layer of the first photovoltaic unit (30) is PEI or PEIE, and has a thickness of 0.5 to 10 nm; the transparent hole transfer layer of the first photovoltaic unit (30) is a mixture of PEDOT and PSS, and has a thickness of 100 to 500 nm; the transparent active layer (32) of the first photovoltaic unit (30) is a mixture of P3HT and PCBM or a mixture of PCPDTBT and PCBM, and has a thickness of 100 to 500 nm; The transparent electron transfer layer of the second photovoltaic unit (40) is a mixture of PEDOT and PSS or is composed of P3HT or PTAA, with a thickness of 100 to 500 nm; the transparent hole transfer layer of the second photovoltaic unit (40) is a mixture of PDPP3T and PCBM, with a thickness of 1 to 100 nm; the transparent active layer (42) of the second photovoltaic unit (40) is a mixture of one of CH3NH3PbI3, CsPbBr3, CsPbI3, FAPbI3, FAPbBr3 or a combination thereof, with a thickness of 200 to 800 nm.
10. The composite photovoltaic structure according to claim 1 or 2, characterized in that: The first photovoltaic unit (30) is a perovskite photovoltaic unit, and the second photovoltaic unit (40) is an organic photovoltaic unit; the transparent electron transfer layer of the first photovoltaic unit (30) is a mixture of PEDOT and PSS or a mixture of P3HT and PCBM, and has a thickness of 100 to 500 nm; the transparent hole transfer layer of the first photovoltaic unit (30) is a mixture of PDPP3T and PCBM, and has a thickness of 1 to 100 nm; the transparent active layer (32) of the first photovoltaic unit (30) is composed of CH3NH3PbI3, CsPbBr3, CsPbI 3. A mixture of one of FAPbI3 and FAPbBr3 or a combination thereof, with a thickness of 200 to 800 nm; the transparent electron transfer layer PEI or PEIE of the second photovoltaic unit (40) has a thickness of 0.5 to 10 nm; the transparent hole transfer layer of the second photovoltaic unit (40) is a mixture of PEDOT and PSS, with a thickness of 100 to 500 nm; the transparent active layer (42) of the second photovoltaic unit (40) is a mixture of P3HT and PCBM or a mixture of PCPDTBT and PCBM, with a thickness of 100 to 500 nm.
11. The composite photovoltaic structure according to claim 1 or 2, characterized in that: The first transparent electrode layer (51) and the second transparent electrode layer (52) are made of ITO, IZO or AZO, and have a thickness of 50 to 200 nm.
12. The composite photovoltaic structure according to claim 1 or 2, characterized in that: The first transparent conductive layer (61) is Ag, Au, Pt or Pd, and has a thickness of 50-200 nm.
13. The composite photovoltaic structure according to claim 1 or 2, characterized in that: The second transparent conductive layer (62) is made of Ag, Au, Pt or Pd, and has a thickness of 50-200 nm.
14. The composite photovoltaic structure according to claim 2, characterized in that: The optical hardening layer (80) is one of acrylic, epoxy resin, silicon dioxide or a combination thereof, and has a thickness of 1 μm to 5 μm.
15. The composite photovoltaic structure according to claim 1 or 2, characterized in that: The first insulating layer (71) and the second insulating layer (72) are polyester high molecular polymers.
16. A method for manufacturing a composite photovoltaic structure, characterized in that: The following steps are involved: a. constructing a transparent electrode layer material (50), providing a transparent substrate (20), and disposing a transparent electrode layer material (50) of a predetermined thickness on the surface of the transparent substrate (20); b. constructing a first photovoltaic unit (30), and sequentially constructing the various layers of material of the first photovoltaic unit (30) on the transparent electrode layer material (50), wherein an upper surface layer (33) and a lower surface layer (31) of the first photovoltaic unit (30) are respectively a transparent electron transfer layer and a transparent hole transfer layer, and a transparent active layer (32) is provided between the upper surface layer (33) and the lower surface layer (31) of the first photovoltaic unit (30); c. constructing a first insulating layer (71), carving at least one first insulating material channel (21) penetrating the transparent electrode layer material (50) on the upper surface of the first photovoltaic unit (30), and filling each of the first insulating material channels (21) with insulating material, so that the first insulating layer (71) is formed in each of the first insulating material channels (21), and each of the first insulating layers (71) separates the transparent electrode layer material (50) into a first transparent electrode layer (51) relatively located below the first photovoltaic unit (30) and a second transparent electrode layer (52) relatively located outside the first photovoltaic unit (30); d. constructing a first transparent conductive layer (61), carving a first transparent conductive material channel (22) from the upper surface layer (33) of the first photovoltaic unit (30) to the transparent electrode layer material (50) at the side position of each first insulating layer (71), and coating the surface of the upper surface layer (33) of the first photovoltaic unit (30) and each of the first transparent conductive material channels (22) with transparent conductive material, so as to form a first transparent conductive layer (61) that is coated on the upper surface layer (33) of the first photovoltaic unit (30) and electrically connected to the first transparent electrode layer (51) along the side of each first insulating layer (71); e. constructing a second photovoltaic unit (40), constructing the various layers of materials of the second photovoltaic unit (40) in sequence on the first transparent conductive layer (61) on the top surface of the first photovoltaic unit (30), wherein an upper surface layer (43) and a lower surface layer (41) of the second photovoltaic unit (40) are respectively a transparent electron transfer layer and a transparent hole transfer layer, and a transparent active layer (42) is provided between the upper surface layer (43) and the lower surface layer (41) of the second photovoltaic unit (40); f. constructing a second insulating layer (72), carving at least one second insulating material channel (23) penetrating to the transparent electrode layer material (50) on the upper surface layer (43) of the second photovoltaic unit (40), and filling each second insulating material channel (23) with insulating material to form the second insulating layer (72) in each second insulating material channel (23); g. constructing a second transparent conductive layer (62), carving a second transparent conductive material channel (24) from the upper surface layer (43) of the second photovoltaic unit (40) to the transparent electrode layer material (50) at the side position of each second insulating layer (72), and coating the surface of the upper surface layer (43) of the second photovoltaic unit (40) and each second transparent conductive material channel (24) with transparent conductive material, so as to form a second transparent conductive layer (62) coated on the upper surface layer (43) of the second photovoltaic unit (40) and electrically connected to the second transparent electrode layer (52) along the side of each second insulating layer (72); h. Finished product segmentation, a cutting channel (25) penetrating to the transparent electrode layer material (50) is carved on the surface of the second transparent conductive layer (62), thereby segmenting and building on the transparent substrate (20) to form at least one composite photovoltaic structure stacked on top of the first photovoltaic unit (30) and connected in parallel with the second photovoltaic unit (40).
17. The method for manufacturing a composite photovoltaic structure according to claim 16, wherein: The composite photovoltaic structure manufacturing method comprises providing an optical hardening layer (80) on the plate surface of the transparent substrate (20), and the transparent electrode layer material (50) is provided on the optical hardening layer (80).
18. The method for manufacturing a composite photovoltaic structure according to claim 16 or 17, characterized in that: The first photovoltaic unit (30) and the second photovoltaic unit (40) are organic photovoltaic units.
19. The method for manufacturing a composite photovoltaic structure according to claim 16 or 17, characterized in that: The first photovoltaic unit (30) and the second photovoltaic unit (40) are perovskite photovoltaic units.
20. The method for manufacturing a composite photovoltaic structure according to claim 16 or 17, characterized in that: The first photovoltaic unit (30) is an organic photovoltaic unit, and the second photovoltaic unit (40) is a perovskite photovoltaic unit.
21. The method for manufacturing a composite photovoltaic structure according to claim 16 or 17, characterized in that: The first photovoltaic unit (30) is a perovskite photovoltaic unit, and the second photovoltaic unit (40) is an organic photovoltaic unit.
22. The method for manufacturing a composite photovoltaic structure according to claim 16 or 17, characterized in that: The first photovoltaic unit (30) and the second photovoltaic unit (40) are organic photovoltaic units; the transparent electron transfer layer of the first photovoltaic unit (30) and the second photovoltaic unit (40) is formed by PEI or PEIE through slit coating and then drying with hot air at 90 to 140° C. for 3 minutes, and has a thickness of 0.5 to 10 nm; the transparent hole transfer layer of the first photovoltaic unit (30) and the second photovoltaic unit (40) is a mixture of PEDOT and PSS diluted with a solvent, and diluted with alcohol After release, the transparent active layers (32) and (42) of the first photovoltaic unit (30) and the second photovoltaic unit (40) are a mixture of P3HT and PCBM diluted with solvent or a mixture of PCPDTBT and PCBM, which are diluted with o-xylene and then slit coated and dried in a nitrogen atmosphere at 90 to 140°C for 3 minutes to form a thickness of 100 to 500 nm.
23. The method for manufacturing a composite photovoltaic structure according to claim 16 or 17, characterized in that: The first photovoltaic unit (30) and the second photovoltaic unit (40) are perovskite photovoltaic units; the transparent electron transfer layer of the first photovoltaic unit (30) and the second photovoltaic unit (40) is composed of a mixture of PEDOT and PSS or of P3HT or PTAA, and is formed by drying at 90 to 140° C. in a nitrogen atmosphere for 5 minutes after slit coating, and has a thickness of 100 to 500 nm; the transparent hole transfer layer of the first photovoltaic unit (30) and the second photovoltaic unit (40) is a mixture of PDPP3T and PCBM. After solvent dilution, the transparent active layers (32) and (42) are formed by slit coating and drying at 90-140°C nitrogen atmosphere for 5 minutes, with a thickness of 1-100 nm. The transparent active layers (32) and (42) of the first photovoltaic unit (30) and the second photovoltaic unit (40) are made of one of CH3NH3PbI3, CsPbBr3, CsPbI3, FAPbI3, FAPbBr3 or a combination thereof, and are diluted with solvent and then slit coated and dried at 90-140°C nitrogen atmosphere for 5 minutes, with a thickness of 200-800 nm.
24. The method for manufacturing a composite photovoltaic structure according to claim 16 or 17, characterized in that: The first photovoltaic unit (30) is an organic photovoltaic unit, and the second photovoltaic unit (40) is a perovskite photovoltaic unit; the transparent electron transfer layer of the first photovoltaic unit (30) is formed by slit coating of PEI or PEIE and drying with hot air at 90-140°C for 3 minutes, and has a thickness of 0.5-10 nm; the transparent hole transfer layer of the first photovoltaic unit (30) is a mixture of PEDOT and PSS diluted by solvent, diluted with alcohol, slit coated, dried in a nitrogen atmosphere at 90-140°C for 5 minutes, and formed by drying, and has a thickness of 100-500 nm; the transparent active layer (32) of the first photovoltaic unit (30) is a mixture of P3HT and PCBM diluted by solvent or a mixture of PCPDTBT and PCBM, diluted with o-xylene, slit coated, dried in a nitrogen atmosphere at 90-140°C for 3 minutes, and formed by drying, and has a thickness of 100- 500nm; the transparent electron transfer layer of the second photovoltaic unit (40) is formed by a mixture of PEDOT and PSS or P3HT or PTAA after slit coating and drying at 90-140°C in a nitrogen atmosphere for 5 minutes, with a thickness of 100-500nm; the transparent hole transfer layer of the second photovoltaic unit (40) is formed by a mixture of PDPP3T and PCBM after being diluted with a solvent and then being slit coated and dried at 90-140°C in a nitrogen atmosphere for 5 minutes, with a thickness of 1-100nm; the transparent active layer (42) of the second photovoltaic unit (40) is formed by a mixture of CH3NH3PbI3, CsPbBr3, CsPbI3, FAPbI3, FAPbBr3 or a combination thereof after being diluted with a solvent and then being slit coated and dried at 90-140°C in a nitrogen atmosphere for 5 minutes, with a thickness of 200-800nm.
25. The method for manufacturing a composite photovoltaic structure according to claim 16 or 17, characterized in that: The first photovoltaic unit (30) is a perovskite photovoltaic unit, and the second photovoltaic unit (40) is an organic photovoltaic unit; the transparent electron transfer layer of the first photovoltaic unit (30) is formed by mixing PEDOT and PSS or P3HT or PTAA through slit coating and then drying at 90-140°C in a nitrogen atmosphere for 5 minutes, and has a thickness of 100-500 nm; the transparent hole transfer layer of the first photovoltaic unit (30) is formed by mixing PDPP3T and PCBM, diluting with a solvent, and then drying at 90-140°C in a nitrogen atmosphere for 5 minutes through slit coating, and has a thickness of 1-100 nm; the transparent active layer (32) of the first photovoltaic unit (30) is formed by mixing one of CH3NH3PbI3, CsPbBr3, CsPbI3, FAPbI3, FAPbBr3, or a combination thereof, and then diluting with a solvent, and then drying at 90 The transparent electron transfer layer of the second photovoltaic unit (40) is formed by slit coating of PEI or PEIE and drying with hot air at 90 to 140°C for 3 minutes, with a thickness of 0.5 to 10 nm; the transparent hole transfer layer of the second photovoltaic unit (40) is a mixture of PEDOT and PSS diluted by solvent, diluted with alcohol, slit coated, and dried in a nitrogen atmosphere at 90 to 140°C for 5 minutes, and then dried to form a thickness of 100 to 500 nm; the transparent active layer (42) of the second photovoltaic unit (40) is a mixture of P3HT and PCBM diluted by solvent or a mixture of PCPDTBT and PCBM, diluted with o-xylene, slit coated, and dried in a nitrogen atmosphere at 90 to 140°C for 3 minutes, with a thickness of 100 to 500 nm.
26. The method for manufacturing a composite photovoltaic structure according to claim 16 or 17, characterized in that: The transparent electrode layer material (50) is made of ITO, IZO or AZO which is evaporated or sputtered on the transparent substrate (20) and has a thickness of 50-200 nm.
27. The method for manufacturing a composite photovoltaic structure according to claim 16 or 17, characterized in that: The first transparent conductive layer (61) is Ag, Au, Pt or Pd, and has a thickness of 50-200 nm.
28. The method for manufacturing a composite photovoltaic structure according to claim 16 or 17, characterized in that: The second transparent conductive layer (62) is formed by evaporation of Ag, Au, Pt or Pd and has a thickness of 50 to 200 nm.
29. The method for manufacturing a composite photovoltaic structure according to claim 17, wherein: The optical hardening layer (80) is one of acrylic, epoxy resin, silicon dioxide or a combination thereof, and has a thickness of 1 μm to 5 μm.
30. The method for manufacturing a composite photovoltaic structure according to claim 16 or 17, characterized in that: The first insulating layer (71) and the second insulating layer (72) are made of polyester high molecular polymer by printing and coating and then dried in hot air at 90-140° C. for 10 minutes.
Citation Information
Patent Citations
Composite photovoltaic structure
CN210576025U